1998
DOI: 10.1002/hep.510270529
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatocellular carcinoma and its incidence after interferon treatment in patients with chronic hepatitis C

Abstract: To elucidate the risk factors for liver carcinogenesis and to examine the incidence of hepatocellular carcinoma (HCC) after interferon therapy, 1,022 chronic hepatitis C patients treated with interferon were followed by ultrasonography for 13 to 97 months (median 36 months). Sustained response with prolonged alanine aminotransferase normalization was found in 313 patients, transient response with alanine aminotransferase relapse after therapy in 304, and no response in 405. Forty-six developed HCC, of whom 5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
400
7
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(431 citation statements)
references
References 55 publications
20
400
7
2
Order By: Relevance
“…7,20 Using multivariate Cox regression analyses, some previous studies demonstrated that fibrosis could be a dependent factor for the development of HCC. 19,21 The previous study confirmed that conclusion.…”
Section: Discussionsupporting
confidence: 68%
“…7,20 Using multivariate Cox regression analyses, some previous studies demonstrated that fibrosis could be a dependent factor for the development of HCC. 19,21 The previous study confirmed that conclusion.…”
Section: Discussionsupporting
confidence: 68%
“…6,9,26 Cirrhosis is the main independent risk factor for HCC development, 9,27 and residual viremia, i.e., HCV-RNA not detected by the currently available commercial PCR assays, may explain the risk of HCC in these patients. 28 The finding that male subjects aged Ͼ54 years have a higher risk of developing HCC suggests that host-related factors and/or the duration of the disease might enhance the risk of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…3 One prospective randomized trial 4 showed reduced HCC incidence in IFN-treated patients with chronic HCV irrespective of virological response, but these results have not been reproduced. A retrospective analysis of a large database in Japan 5 and other small studies [6][7][8] designed to assess the rate of SVR following IFN therapy have not provided conclusive evidence that the progression of liver disease underling HCV infection was halted in nonresponder patients.…”
mentioning
confidence: 99%
“…21 Most of the studies to date have examined the effect of interferon at standard doses for 6 to 12 months. 23,24 The possible effects of prolonged therapy have not been studied nor has the combination of interferon and ribavirin. A National Institutes of Health-funded study that aims to address this question has been initiated (the HALT-C trial).…”
Section: Prevention Of Disease Progression and Hccmentioning
confidence: 99%